Exploitation of insect vibrational signals reveals a new method of pest management. - Anna Eriksson (Public Library of Science (PLoS), 2012)
Food production is considered to be the main source of human impact on the environment and the concerns about detrimental effects of pesticides on biodiversity and human health are likely to lead to an increasingly restricted use of chemicals in agriculture. Since the first successful field trial, pheromone based mating disruption enabled sustainable insect control, which resulted in reduced levels of pesticide use. Organic farming is one of the fastest growing segments of agriculture and with the continuously growing public concern about use of pesticides, the main remaining challenge in increasing the safety of the global food production is to identify appropriate alternative mating disruption approaches for the numerous insect pests that do not rely on chemical communication. In the present study, we show for the first time that effective mating disruption based on substrate-borne vibrational signals can be achieved in the field. When disruptive vibrational signals were applied to grapevine plants through a supporting wire, mating frequency of the leafhopper pest Scaphoideus titanus dropped to 9 % in semi-field conditions and to 4 % in a mature vineyard. The underlying mechanism of this environmentally friendly pest-control tactic is a masking of the vibrational signals used in mate recognition and location. Because vibrational communication is widespread in insects, mating disruption using substrate vibrations can transform many open field and greenhouse based farming systems.